APLIKASI METODE ADAMS BASHFORTH-MOULTON (ABM) PADA MODEL PENYAKIT KANKER - Kuzairi Kuzairi; Tony Yulianto; Lilik Safitri (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2016)
Cancer is a deadly disease that is characterized by the growth of abnormal cells, the growth is ongoing, forming a tumor. Tumors are divided into two parts, namely benign and malignant tumors. Malignant tumors are a general term for cancer. The disease of cancer has a mathematical model in the form of a system of differential equations, for it required a method to obtain the solution of the system of differential equations. The method used is the method of numerical methods Bashforth Adams Moulton (ABM) order one, two, three, and four. From the results of this study concluded that the method ABM order three better than the method ABM first order, second order and fourth order at issue models of cancer, It can be seen in the graphic simulation using ABM order three, it shows that increasing time population of immune effector cells (E) and a population of effector molecules (C) increased and then stabilized. The population of immune effector cells (E) stabilized at 33.3336, while the population of the effector molecule (C) is stable in the scope of the numbers 33,333, 33,333 are said to be in scope for changes in population effector molecule (C) can not be known with certainty. While the population of cancer cells (T) remains at 0 at each iteration (stable) remains in a state that is free of cancer